Cascade chiral amine synthesis catalyzed by site-specifically co-immobilized alcohol and amine dehydrogenases. Issue 14 (9th June 2022) - Liu, Si; Wang, Zhenfu; Chen, Kun; Yu, Linling; Shi, Qinghong; Dong, Xiaoyan; Sun, Yan
Abstract : Sustainable and efficient production of chiral amines was realized with an oriented co-immobilized dual-enzyme system via SiBP-tag. Abstract : Chiral amines are valuable intermediates widely applied in the pharmaceutical industry. As an alternative to classical synthetic methods for the production of chiral amines, biocatalytic cascade synthesis for these molecules from their alcohol precursors has been developed. However, currently available enzyme cascade systems remain unstable and unsustainable in the practice of chiral amine synthesis. Herein, the catalytic cascade system of chimeric amine dehydrogenase (AmDH) and alcohol dehydrogenase (ADH) fused with silica binding peptide (SiBP) was site-specifically co-immobilized on silica nanoparticles (SNPs). SiBP enabled the fusion enzymes to firmly bind to SNPs, and both the single immobilized enzymes showed higher catalytic efficiencies ( k cat / K m ) than their free counterparts to different degrees. Using 10 mM ( S )-2-hexanol as the substrate, the co-immobilized enzyme system (SiBP–ADH&SiBP–AmDH@SNPs) showed 90% ( R )-2-aminohexane yield after 48 h reaction, which was 1.85-fold higher than the free enzyme system due to the enhanced catalytic efficiency of the immobilized enzymes and the possible proximity effect of the SiBP–ADH&SiBP–AmDH@SNPs. The catalyst productivity of the SiBP–ADH&SiBP–AmDH@SNPs was 11 to 34 times higher than literature data, demonstrating the high economic benefits and catalytic efficiency of this system in producing chiral amines. SiBP–ADH&SiBP–AmDH@SNPs retained 87% of its original activity after eight cycles of reuse. These results highlighted the potential of the co-immobilization system for the effective and sustainable synthesis of chiral amines in industrial practice.